Review on the in vitro cytotoxicity assessment in accordance to the International Organization for Standardization (ISO) - Mohd Shafiee, Muhammad Aminuddin; Muhamad Asri, Mohd Ashraf; Syed Alwi, Sharifah Sakinah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2021)
Cytotoxicity is a predominant biological evaluation applied to search for a suitable and non-toxic bioactive compound and to determine the biocompatibility of medical devices-related human body. The broad usage of cytotoxicity tests leads to a robust establishment of cytotoxicity assays with high sensitivity and prompt results. In vitro assays are always prioritized over in vivo due to the reproducible data, reduce numbers of animal used and easily accessible material. Compounds concentration that execute 50% of cell population is determined by calculating the IC50. According to ISO10993, cytotoxicity tests must be performed to determine the biocompatibility of medical devices that has contact with human body. This is crucial to ensure the safety of research and its clinical use. Under the recommendation of ISO10995-Part 5, three categories of tests have been documented; extract elution, direct contact and indirect contact test. Each category plays significant role depending on the nature of experiment and sample used.